PENGEMBANGAN POTENSI PERKEBUNAN MANGGIS WANAYASA SEBAGAI KAWASAN WISATA AGRO DI KABUPATEN PURWAKARTA - Yayan Mulyana, - (2009)
In line with dynamics, the motion of international tourism development enters 20th century slowly changed from mass tourism to become individual tourism or green tourism. The movements followed by the increasing of world public awareness about environmental that make change the tourist market profile. Tourist becomes more concern about cultural and environment surround them so their tourism activity in natural tourism object which provide cultural attraction doing more often in frequently. This tendency makes nature tourism object such as eco-tourism and agro tourism become increasingly popular as alternative tourism. So, special interest tourism is a new form of tourism caused by request from tourist market profile which has been changed at present. Special interest tourism is not only doing activity of ordinary vacation. Special interest tourist tended to make their journey with a purpose of self development, take care of certain morality and values. One of special interest tourism is agro tourism. In this research, researcher applied the descriptive analysis method where researcher only defines in detail without adding of more and words reduction. Others in this research applied the qualitative approach and its instrument is society which has been determined by researcher. In determining supplementary factor and resistor factor in development of area of agro tourism the researcher used SWOT analysis. The development which suited for applied at mangosteen plantation of Wanayasa is development based on conservation, that is development through construction pattern which remain to maintains authenticity of agro-ecosystem by striving continuity of environment natural resources, history, culture, and recreation.